Dichlorobenzene: an effective solvent for epoxy/graphene nanocomposites preparation. Issue 10 (11th October 2017) - Wei, Jiacheng; Saharudin, Mohd Shahneel; Vo, Thuc; Inam, Fawad
Abstract : It is generally recognized that dimethylformamide (DMF) and ethanol are good media to uniformly disperse graphene, and therefore have been used widely in the preparation of epoxy/graphene nanocomposites. However, as a solvent to disperse graphene, dichlorobenzene (DCB) has not been fully realized by the polymer community. Owing to high values of the dispersion component ( δ d ) of the Hildebrand solubility parameter, DCB is considered as a suitable solvent for homogeneous graphene dispersion. Therefore, epoxy/graphene nanocomposites have been prepared for the first time with DCB as a dispersant; DMF and ethanol have been chosen as the reference. The colloidal stability, mechanical properties, thermogravimetric analysis, dynamic mechanical analysis and scanning electron microscopic images of nanocomposites have been obtained. The results show that with the use of DCB, the tensile strength of graphene has been improved from 64.46 to 69.32 MPa, and its flexural strength has been increased from 97.17 to 104.77 MPa. DCB is found to be more effective than DMF and ethanol for making stable and homogeneous graphene dispersion and composites.